THE USE OF DICTIONARIES OF THE RUSSIAN LANGUAGE IN HIGHER TECHNICAL EDUCATION (American Journal of Pedagogical and Educational Research, 2023)
This article describes the methods of using dictionaries and effective learning of the Russian language in higher technical education. Talking with Russian speakers goes beyond learning the language. This opens up opportunities to immerse yourself in Russian culture, build connections and friendships, and stay abreast of the evolution of the language. So is taking the opportunity to interact with native speakers and embark on a rewarding journey of language learning, cultural appreciation, and personal growth.